Effect of Side Groove Shapes on Shear Lips Formation of Aluminium Alloy 6061 using Finite Element Analysis - Mohd Al-Hatta, Muhammad Al-Fayyidh; Harimon, Mohd Azhar (Journal of Advanced Mechanical Engineering Applications, 2022)
Aluminium alloy 6061 is known for its superior mechanical characteristics which include lighter weight properties, simple fabrication, and high specific strength of aluminium alloys. Hence, they are widely used to reduce the weight of vehicles as structural parts. Aluminium alloy 6061 is exposed to high velocity and various forces during an accident. Hence, understanding the impact properties of aluminium alloys is critical. This study investigated the effect of side groove shapes on the shear lip growth of aluminium alloy 6061. The shapes of the side groove in this study are V-shape, U-shape, and square-shape. By simulation using Abaqus software, the Charpy impact test was conducted to determine the shear lips ratio, energy absorbed, displacement and force. It was found that the V-shape side groove shape has the lowest absorb energy as compared to the U-shape and square shape. The low absorbed energy indicates that the behaviour of the sample test is in a fast-moving brittle fracture. Furthermore, it can be observed that the shear lips for V-shape and square-shape have the lowest ratio of shear lips when compared to the U-shape of the side groove. The smaller the shear lips ratio of a certain material, the higher it tends to reach brittle. In conclusion, when the shear lips ratio is low, it will tend to be low ductility of aluminium alloy 6061, the energy absorbed is low and the impact of the force is also low.